2016
DOI: 10.1007/s10897-016-9976-3
|View full text |Cite
|
Sign up to set email alerts
|

“The Top Priority Is a Healthy Baby”: Narratives of Health, Disability, and Abortion in Online Pregnancy Forum Discussions in the US and China

Abstract: The introduction of cell-free DNA prenatal genetic screening has rekindled discussion of ethical and social questions surrounding prenatal testing, perceptions of disability, and abortion. The growing use of prenatal genetic screening presents a unique opportunity to assess decision-making around new methods of prenatal testing; especially as there is little available research comparing individual and cultural differences that affect a pregnant woman's decision-making on prenatal testing. We performed a conten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 35 publications
(30 reference statements)
0
21
0
Order By: Relevance
“…As we were only searching open‐access forums in the English language, our study is likely to be an underrepresentation of the number of discussion forums regarding NIPT. Furthermore, if we had included specific NIPT brands in our search terms the number of discussion forums may have been higher (cf search by Li et al).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As we were only searching open‐access forums in the English language, our study is likely to be an underrepresentation of the number of discussion forums regarding NIPT. Furthermore, if we had included specific NIPT brands in our search terms the number of discussion forums may have been higher (cf search by Li et al).…”
Section: Discussionmentioning
confidence: 99%
“…Shopping terminologies were evident in the acquisition of NIPT and our findings similar to those found by Li et al and Bowman-Smart et al who reported women discussing "spending money to buy peace of mind". 11,23 On their website, Harmony describe how NIPT can be used "For your baby's health and your peace of mind," and BGI's brands Nifty as "Prenatal peace." It is therefore not surprising to see women echoing this same language.…”
Section: Access To Niptmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample in this study is largely composed of white, married women with high socioeconomic status and educational attainment, and therefore does not account for how variations in race, socioeconomic status, and education may shape experiential knowledge and factor into NIPT use decision-making. Future studies should aim to evaluate this framework of decision-making in more diverse samples [37,38,9].…”
Section: Limitationsmentioning
confidence: 99%
“…The main reason for the predominantly hearing Chinese population to seek prenatal testing is to have a hearing baby. This is assumed, because a respondent was only asked to explain if not interested [Fu et al, ], but it has been shown that the top priority is a healthy baby for Chinese couples [Li et al, ]. In contrast, being able to prepare for having a deaf child was the primary reason for testing given by most parents of deaf children in the United States [Brunger et al, ].…”
mentioning
confidence: 99%